Developing a Virtual Chemistry Practicum Platform for University Students: Validity, Practicality, and Implementation Insights - Muhammad Qaddafi; Anas Irwan; Santih Anggereni; Ali Umardani; Diki Harbis (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study aimed to develop and evaluate a virtual chemistry practicum tool that meets criteria of validity, effectiveness, and practicality in higher education.RD approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed. The prototype was tested with 8 laboratory assistants and 22 Physics Education students at UIN Alauddin Makassar enrolled in basic chemistry, and validated by two experts. Instruments included expert validation sheets, observation sheets, student response questionnaires, and a concept-understanding test. Content validity was analyzed using the Gregory index (Aiken’s V), while effectiveness and practicality were assessed through descriptive statistics.The virtual practicum platform demonstrated high validity (Aiken’s V = 0.74), indicating it is feasible for use. Effectiveness was supported by learning outcomes, with 78% of students achieving scores ≥70. Practicality was rated “very good” based on student responses. The platform integrates attendance management, assignment submission, assessment features, and video- and animation-based practicum guides that enhance procedural understanding.The developed tool facilitates practicum management and improves student engagement and task completion. Its strong validity, effectiveness, and practicality suggest it is a viable alternative to traditional laboratory instruction. This study contributes to the advancement of technology-enhanced chemistry education and supports broader adoption of virtual laboratory environments in higher education.